Spontaneous regression of a pulmonary adenocarcinoma after core needle biopsy - Marques, Cristiana; Queiroga, Henrique; Marques, Margarida; Moura, Conceição (Autopsy and Case Reports, 2017)
Spontaneous regression (SR) of cancer, especially lung cancer, is a rare biological event with a mechanism that is not currently understood. Immunological mechanisms seem to be the stronger explanation in SR of a lung cancer. We report the rare case of SR of a lung adenocarcinoma stage IA, in a 75-year-old man, which was incidentally diagnosed and histologically confirmed. Due to the patient’s comorbidities and his poor pulmonary function, stereotactic radiotherapy was scheduled. However, by the time the treatment was due to start, the tumor was no longer detectable